Ultra-processed food consumption and obesity in adolescents - ENES, Carla Cristina; Moura de CAMARGO, Carolina; Coelho JUSTINO, Maraisa Isabela (Revista de Nutrição, 2023)
Objective To evaluate the relationship between ultra-processed food consumption and obesity indicators in adolescents. Methods Cross-sectional study with a convenience sample of 200 10- to 18-year-old adolescents from Campinas, São Paulo (SP). Usual dietary intake was determined through a semiquantitative food frequency questionnaire. Daily intake of each food was obtained from the intake frequency. Subsequently, foods were classifi ed as raw and minimally processed, cooking ingredients or ultra-processed foods, and their caloric contribution to the total energy value was calculated. Sociodemographic and anthropometric variables were also investigated. Overweight was defi ned as Z-score>+1 and obesity was defi ned as Z-score>+2 according to the Body Mass Index per age group. The associations were tested by chi-square test and linear trend. Results The frequency of obesity was 47.0%, and 21.5% presented increased waist circumference. The average energy intake was 4,176kcal/day, of which 50.6% was derived from ultra-processed foods. The categories with the highest caloric contributions among ultra-processed foods were industrial loaves/cakes (16.2%), sweets and candy (6.2%), pastas (6.0%) and sweetened drinks (5.1%). No association was found between ultra-processed food consumption and anthropometric indicators. Conclusion The significant contribution of ultra-processed foods to daily calories is evidence of a poor diet of this population of young people, although this has not been shown as a factor associated with excess weight. Therefore, there is an urgent need for public policies that discourage the consumption of these products and encourage the return to a traditional diet.